Analysis of Diabetes Mellitus Risk Factors in Blitar Regency - Mayasari, Ema; Indahyati, Nanik (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2021)
Diabetes mellitus is a serious chronic disease that occurs because the pancreas does not produce enough insulin, or when the body cannot effectively use the insulin it produces. Risk factors for DM are age, gender, family history, obesity, central obesity, hypertension, dyslipidemia, lack of physical activity, unhealthy diet and smoking. Indonesia was ranked the sixth highest prevalence of Diabetes Mellitus in the world in 2017, namely 2%, East Java 2.6% and Blitar Regency 2.6%. The high prevalence rate of DM in Blitar Regency which exceeds the national prevalence is a challenge that must be faced, because the target of the Sustainable Development Goals (SDGs) in 2030 is a reduction of one third of premature deaths due to non-communicable diseases. The purpose of this study was to analyze the risk factors for Diabetes Mellitus in Blitar Regency. Method using Quantitative research design, using secondary data with the Non-Probability Purposive Sampling method, the number of samples of 400 samples and analyzed using the Case Control method. The results of statistical tests showed that age, family history, obesity, central obesity and hypertension were associated with DM. While gender is not related to the incidence of DM. Based on the results of the multivariate test, it is known that the most dominant factors affecting the incidence of DM in Blitar Regency are family history, age> 45 years, hypertension, and central obesity. It is suggested that future studies use a longitudinal cohort design to determine whether risk factors actually correlate with effect factors and to see a clear causal relationship.